Alteration of Porcine Intestinal Microbiota in Response to Dietary Manno-Oligosaccharide Supplementation - Yu, En; Chen, Daiwen; Yu, Bing; Huang, Zhiqing; Mao, Xiangbing; Zheng, Ping; Luo, Yuheng; Yin, Heng; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun (Frontiers in Microbiology, 2022)
Manno-oligosaccharide (MOS) is a prebiotic derived from natural plants or yeasts. Here, we explored the response of intestinal microbiota and epithelial functions after ingestion of MOS in a porcine model. Sixteen pigs were randomly assigned into two treatments and fed with basal or MOS-containing (0.3% MOS) diet for 21 d. Results showed that MOS supplementation increased the cecal acetate content and ileal 16S rRNA gene copies (p < 0.05). Importantly, MOS decreased the abundance of phylum Proteobacteria in cecal digesta (p < 0.05). Moreover, MOS elevated the expression level of SCL5A8 and GPR109A but decreased the expression levels of HDAC1 and TNF-α in the ileal and cecal mucosa (p < 0.05). MOS up-regulated the expression levels of tight-junction protein (ZO-1, Claudin-1 and Occludin) and IGF-1 in the ileum and cecum (p < 0.05). This study presented the alteration of intestinal microbiota composition and intestinal barrier function after MOS administration, and facilitate our understanding of the mechanisms behind the dietary MOS-modulated intestinal microbiota and health.